Effect of tilt angle selection on the performance of grid-connected photovoltaics: Turkey case study - Ekici, S. (Natl Inst Optoelectronics, 2016)
The purpose of this article is to constitute awareness about solar PV panels and investigate the effect of tilt angles on the performance at different latitudes of Turkey where the active solar systems are not widely used. The monthly average global and diffuse solar radiations of the locations were calculated numerically. A two-step screening was carried out for detecting the annual optimum tilt angles. Firstly a search between 0 degrees and 75 degrees with 5 degrees steps, then a deeper analysis between 28 degrees and 40 degrees with 1 degrees steps was employed. Then the monthly and seasonal optimum tilt angles were determined. Monthly and annual energy yield of the PV installations were obtained by using PVSyst 5.0 software. The monthly, seasonally and the yearly optimum tilt angles were detected for each locations. As a result it's found out that, the yearly optimum tilt angles for Antakya, Elazig and Sinop are 32.1 degrees, 34.6 degrees and 37.9 degrees respectively. It is also found that mounting the panels at the monthly average tilt angles increase the energy output of PV systems with the ratios of % 5.2 for Antakya, % 6 for Elazig and % 6.3 for Sinop.
Keywords: Grid-connected photovoltaics; Solar radiation; Optimum tilt angle; PVSyst; Electricity production